ANALISIS LITERASI PERBANKAN SYARIAH PADA PELAKU UMKM INDUSTRI MAKANAN KHAS DI DESA SUKAJADI KECAMATAN SADANANYA KABUPATEN CIAMIS - Nurfaisyal Suryaeltarlan; Harun Nur Jamiel; Dede Lutfi Mubarok (KHITABAH: Khazanah Penelitian Perbankan Syariah, 2026)
The low integration between the real sector of MSMEs and Islamic financial institutions in rural areas is often rooted in a massive literacy gap. This study aims to analyze in-depth the level of Islamic banking literacy among MSMEs in the traditional food industry in Sukajadi Village, Sadananya District, Ciamis Regency, and to examine the inhibiting factors that contribute to the low adoption of Islamic financial services. This study used a qualitative approach with descriptive analytical methods through in-depth interviews, participant observation, and documentation with ten informants who are traditional food business owners. The results show that the Islamic banking literacy of MSMEs in Sukajadi Village is still in the not-literate to less-literate phase. Although the majority of informants have a basic awareness of the physical existence of Islamic banks, they experience epistemological disruptions related to contract instruments and basic principles such as the prohibition of usury. This gap is triggered by the existence of cognitive accessibility barriers to the terminology of muamalah fiqh, which is considered complicated, and the absence of inclusive education from Islamic financial institutions, which tend to be passive at the grassroots level. As a result, business actors are trapped in "Pragmatic Resistance," where they prefer to persist with informal funding patterns, perceived as more practical, rather than migrate to the Islamic banking system. These findings confirm that the religious jargon of rural communities cannot be converted into inclusive financial behavior without a simplified contract structure and a more down-to-earth educational approach. This research contributes to the development of Islamic economics literature by offering a new paradigm regarding the urgency of a localized approach to terminology in financial literacy strategies for rural communities.